A CD10‐OGP Membrane Peptolytic Signaling Axis in Fibroblasts Regulates Lipid Metabolism of Cancer Stem Cells via SCD1. Issue 19 (7th August 2021) - Yu, Shubin; Lu, Yiwen; Su, An; Chen, Jianing; Li, Jiang; Zhou, Boxuan; Liu, Xinwei; Xia, Qidong; Li, Yihong; Li, Jiaqian; Huang, Min; Ye, Yingying; et al.
Abstract: Carcinoma‐associated fibroblasts (CAFs) consist of heterogeneous subpopulations that play a critical role in the dynamics of the tumor microenvironment. The extracellular signals of CAFs have been attributed to the extracellular matrix, cytokines, cell surface checkpoints, and exosomes. In the present study, it is demonstrated that the CD10 transmembrane hydrolase expressed on a subset of CAFs supports tumor stemness and induces chemoresistance. Mechanistically, CD10 degenerates an antitumoral peptide termed osteogenic growth peptide (OGP). OGP restrains the expression of rate‐limiting desaturase SCD1 and inhibits lipid desaturation, which is required for cancer stem cells (CSCs). Targeting CD10 significantly improves the efficacy of chemotherapy in vivo. Clinically, CD10‐OGP signals are associated with the response to neoadjuvant chemotherapy in patients with breast cancer. The collective data suggest that a nexus between the niche and lipid metabolism in CSCs is a promising therapeutic target for breast cancer. Abstract : CD10, a transmembrane hydrolase expressed by a subset of carcinoma‐associated fibroblasts, drives tumor progression by degrading an anti‐tumoral peptide, osteogenic growth peptide (OGP). OGP impairs tumor lipid desaturation and consequently suppresses cancer stem cells (CSCs). This study sheds new light on a nexus between the niche and lipid metabolism in CSCs.